1999
DOI: 10.1054/jhsb.1999.0069
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Histology of the Annular and Cruciform Pulleys

Abstract: Twenty annular and 12 cruciform pulleys were dissected from four unembalmed fresh cadaveric fingers and stained with haematoxylin and eosin, Verhoeff-van Gieson stain for elastin, alcian blue stain for hyaluronic acid, and a separate stain for S-100 to identify chondroid cells. Three distinct layers were identified in both annular and cruciform pulleys: an outer layer of fibrofatty tissue with vascular channels outermost, an inner layer of hyaluronic acid-secreting cells, and a collagen-rich layer in between. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…The combination of elastic component and hyaluronan has been considered to be an adaptation to vibration of the vocal fold. In the human body, the same combination of substances has also been reported in the annular and cruciform pulleys of the finger (Katzman et al. 1999), the extensor retinaculum of the wrist and ankle (Klein et al.…”
Section: Discussionsupporting
confidence: 57%
“…The combination of elastic component and hyaluronan has been considered to be an adaptation to vibration of the vocal fold. In the human body, the same combination of substances has also been reported in the annular and cruciform pulleys of the finger (Katzman et al. 1999), the extensor retinaculum of the wrist and ankle (Klein et al.…”
Section: Discussionsupporting
confidence: 57%
“…In the case of SpA, disease models based on the concept of fibrocartilage autoimmunity have recently been proposed [22,41]. However, an equally tenable view that is independent of fibrocartilage autoimmunity has been proposed [7•].…”
Section: Therapy For Enthesitismentioning
confidence: 99%
“…Many authors have described this pulley as having only two layers (Doyle, 1990;Lundborg and Myrhage, 1977;Sampson et al, 1991) while others have reported three layers in adults (Ellis et al, 1995;Eskeland et al, 1977;Katzman et al, 1998Katzman et al, , 1999Moutet, 2002) and in the embryonic hand (Sbernardori et al, 2000), with the inner one having a continuous synovial cellular layer (Cohen and Kaplan, 1987). A few authors have also described the presence of ''chondrocyte-like cells'' with a positive cytoplasmic reaction for S-100 protein in normal and trigger fingers (Katzman et al, 1999;Sampson et al, 1991). The presence of 'chondroid-metaplasia' has also been reported by Nakamichi and Tachibana (1998) in a histological study of the transverse carpal ligament and in the tendon sheaths in patients with De Quervain's disease (Buchman et al, 1990;Clarke et al, 1998;Meachim and Roberts, 1968).…”
mentioning
confidence: 99%